My brother Sam is dead - Collier, James Lincoln, 1928-; Collier, Christopher, 1930-2020. (New York : Scholastic, 2005)
Recounts the tragedy that strikes the Meeker family during the Revolution when one son joins the rebel forces while the rest of the family tries to stay neutral in a Tory town.
"Apple Signature."
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Challenged books